STRUKTUR DAN NILAI BUDAYA CERITA RAKYAT ANEUK JAMEE MALIMDIWA - Fitriandi Fitriandi (TELAGA BAHASA, 2017)
This study aimed to describe cultural values contained in the story. Thisresearch was qualitative research with descriptive method. Data collectiontechniques in this research was the study of the techniques of documentary.Cultural values found in this story was cultural values in relation to God,nature, society, other people and themselves.